'Agency is Everywhere': An encounter with Hans-Jörg Rheinberger. (2nd April 2020) - Hauser, Jens; Strecker, Lucie
Abstract : In this encounter, historian and philosopher of science Hans-Jörg Rheinberger discusses to what extent the performative paradigm can be made useful for understanding the natural sciences and how the different notions of performativity transpire in interdisciplinary and art–science collaborations. In conversation with issue editors Jens Hauser and Lucie Strecker, and against the grain of the 'two cultures' thesis assumption that the natural sciences and the humanities have grown apart into fields of knowledge that can no longer understand each other, Rheinberger approaches the notion of microperformativity in the light of scientific experimentation. He is putting the focus less on the action of the human experimenter than on the agency of the non-human dimensions involved: substances and organisms are staged to interact with each other, or environments are created to initiate processes in which these interactions can take place—and from which the experimenter can withdraw. Therefore, in the laboratory, two performance contexts and concepts collide. In the experimental process, endless feedback loops are created through the interaction, for instance, between human performers and viruses, which attack bacteria, get them to burst and thus generate forms of technically controlled visualization – by 'compression' and 'dilatation': Microperformativity implies a sensitization not only to other levels of spatiality but also of temporality than those accessible to the mesoscopic phenomenology of the human, which correspond to the established concept of performativity in art and theatre studies, linguistics and anthropology. In addition, the conversation takes a look at the agential relationships between the micro-, meso- and macrocosmic dimensions with regard to the much-cited term 'Anthropocene': An analysis of the performativity of both non-human actors and human technology results in a reversion of the notion of performance: The globe, the planet is striking back—and it is no longer primarily the people who are acting.